References in Speech of Selena Gomez Billboard Music Award: Discourse Analysis Study - Widya Setyowati; Puspita Sari (Linguistic, English Education and Art (LEEA) Journal, 2024)
The purpose of this study is to analyze the function of references within Selena Gomez's Billboard Woman of the Year speech through a comprehensive analysis. The research employs a qualitative descriptive method, with data obtained from a YouTube video posted by the Global TV team on December 2, 2018. To analyze the data, this research utilizes discourse analysis theory from Halliday and Hasan (2013). The study focuses on identifying types of references and what grammatical cohesion is found in each type of reference within the framework of discourse analysis. The distribution of found references is as follows: 49 (35.8%) data for anaphoric reference, 16 (11.7%) for cataphoric reference, and 5 (3.6%) for exophoric reference. In terms of grammatical cohesion, the data are distributed as follows: 32 (23.4%) data for pronouns, 33 (24.1%) for lexical cohesion, and 1 (0.7%) for ellipsis. The study employs systemic functional linguistics (SFL) to delve into speech functions, emphasizing the importance of grammar and language in effective communication. By examining Selena Gomez's speech, the research aims to uncover underlying meanings and cultural influences embedded in her references. Discourse analysis, as a tool, allows for a broader understanding of language's role in society communication, particularly within the realm of celebrity culture. Keywords: Anaphoric, Cataphoric, Exophoric, Discourse Analysis, Reference, Youtube Video